Analysis of soluble interleukin-2 receptor as a prognostic biomarker in NMOSD and MOGAD - Klyscz, Philipp; Otto, Carolin; Ruprecht, Klemens; Asseyer, Susanna; Tiedt, Hannes Ole; Meisel, Christian; Bellmann-Strobl, Judith; Paul, Friedemann; Schindler, Patrick (Annals of Clinical and Translational Neurology, 2025)
Objective Soluble interleukin-2 receptor (sIL-2R) is a biomarker for T cell activity. T cells are involved in neuromyelitis optica spectrum disorders (NMOSD) and myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) pathogenesis. However, sIL-2R has so far not been evaluated in these conditions. Here, we compared sIL-2R levels in serum and cerebrospinal fluid (CSF) of patients with aquaporin-4-IgG-seropositive and seronegative (AQP4-IgG+/−) NMOSD, MOGAD, and noninflammatory neurologic disorders (NINDs), and assessed the prognostic value of sIL-2R for future attacks. Methods Retrospective analysis of real-world data of patients treated at Charité—Universitätsmedizin Berlin was conducted (45 MOGAD, 14 AQP4-IgG+NMOSD, 10 AQP4-IgG−NMOSD, 69 NINDs) between 2010 and 2024. Mean (SD) follow-up time was 40 (35) months. sIL-2R differences were assessed by linear mixed models. Cox regression analysis was performed to investigate the predictive value for subsequent attacks. Results Serum sIL-2R was higher in AQP4-IgG+NMOSD (estimated marginal mean [EMM] 802 IU/mL) and MOGAD (569 IU/mL) compared to NINDs (404 IU/mL). In patients with a first manifestation of MOGAD, but not NMOSD, serum sIL-2R (HR = 9.07 [95% CI 1.37-60.01]) and CSF sIL-2R (HR = 3.27 [95% CI 0.61-17.45]) levels were predictive for subsequent attacks. Interpretation Serum sIL-2R is elevated in AQP4-IgG+NMOSD and MOGAD and may be a prognostic biomarker for a relapsing disease course in MOGAD.